Comparison of prednisolone acetate 1.0% and difluprednate ophthalmic emulsion 0.05% after cataract surgery: Incidence of postoperative steroid‐induced ocular hypertension. Issue 2 (February 2017) - Tijunelis, Marius A.; Person, Erica; Niziol, Leslie M.; Musch, David C.; Ernest, Paul; McBain, Madeline; Mian, Shahzad I.
Abstract : Purpose : To compare intraocular pressure (IOP) outcomes between 2 common, commercially available corticosteroid drops: difluprednate ophthalmic emulsion 0.05% and prednisolone acetate 1.0%. Setting : TLC Eyecare and Laser Centers, Jackson, Michigan, USA. Design : Retrospective chart review. Methods : The outcomes of consecutive patients who had uneventful cataract surgery from April 2013 to September 2013 and used prednisolone acetate postoperatively were compared with the outcomes of consecutive patients who had uneventful cataract surgery from June 2014 to October 2014 and used difluprednate postoperatively. Results : The study included 224 eyes treated with prednisolone acetate 4 times daily for 30 days and 225 eyes treated with difluprednate 2 times daily for 30 days. There was no significant difference between the 2 groups in age, sex, or race. In addition, the mean IOP did not differ significantly between the prednisolone acetate group and the difluprednate group at the preoperative measurement or 1 month after surgery, nor was there a difference in the 1‐month change in IOP between groups. No association was found between the incidence of a 6 mm Hg or higher increase in IOP 1 month after surgery and steroid treatment. One month postoperatively, 4 eyes in the prednisolone acetate group and 5 eyes in the difluprednate group had an IOP higher than 21 mm Hg. Conclusions : There was no significant difference in the mean IOP or percentages showing IOP elevation between eyes treated with difluprednate and eyes treated with prednisolone acetate after cataract surgery. This was likely the result of low‐frequency dosing and short duration of steroid use.